aCGH analysis reveals novel mutations associated with congenital diaphragmatic hernia plus (CDH+) - Schreiner, Yannick; Stoll, Teresa; Nowak, Oliver Claudius; Weis, Meike; Hetjens, Svetlana; Steck, Eric; Perez Ortiz, Alba; Rafat, Neysan (Journal of Clinical Medicine, 2023)
Congenital diaphragmatic hernia (CDH) is a major birth anomaly that often occurs with additional non-hernia-related malformations, and is then referred to as CDH+. While the impact of genetic alterations does not play a major role in isolated CDH, patients with CDH+ display mutations that are usually determined via array-based comparative genomic hybridization (aCGH). We analyzed 43 patients with CDH+ between 2012 and 2021 to identify novel specific mutations via aCGH associated with CDH+ and its outcome. Deletions (n = 32) and duplications (n = 29) classified as either pathological or variants of unknown significance (VUS) could be detected. We determined a heterozygous deletion of approximately 3.75 Mb located at 8p23.1 involving several genes including GATA4, NEIL2, SOX7, and MSRA, which was consequently evaluated as pathological. Another heterozygous deletion within the region of 9p23 (9,972,017-10,034,230 kb) encompassing the Protein Tyrosine Phosphatase Receptor Type Delta gene (PTPRD) was identified in 2 patients. This work expands the knowledge of genetic alterations associated with CDH+ and proposes two novel candidate genes discovered via aCGH.
Gesehen am 21.08.2024